(untitled) (Heritage, 2022)
The modern-age coffin-reliquary of the Holy King Stefan of Dečani was made at Dečani Monastery in 1849. It is believed to have been made and wood-carved by the woodworker Dimitar Stanišev of Kruševo and painted by the icon-painter Anastas Konstantinović. It is shaped like a four-legged sarcophagus, gilded and ornately decorated with woodcarvings enveloping painted fields with narrative scenes and portraits of Serbian saints. Among other images, the lid features 31 circular medallions with painted busts of Serbian rulers and church dignitaries. The visual exemplars for the shaping of these painted medallions were the Stematografija by Hristifor Žefarović and his copper plates “St. Sava with the Serbian saints from the house of Nemanja” and “The Branković saints of Srem.” The selection of the depicted saints and their iconography suggest that the painter was certainly familiar with the copper plates from the Rimnica and Venetian Srbljak. In addition, the artist had the iconostasis in the parekklesion of St. Demetrios, created in 1813, right in front of him, in the church. However, the lid of the Dečani coffin-reliquary features a much larger number of saints than the iconostasis and the Stematografija. And yet, the repertoire of saints on the coffin-reliquary does not include some of those shown on the iconostasis, such as Archbishop Danilo and St. Basil/Vasilije of Ostrog. The most distinctive characteristic of this selection of saints is repetition – some saints were painted twice. A noticeable effort was made to find a way to group the shown saints, so, in a few places those shown in pairs in the Stematografija appear one next to another here, too. Female saints are also grouped together, including the Holy Empress Helena, who had a special place in the visual culture of the 19th century. The coffin-reliquary of the Holy King Stefan of Dečani is a remarkable example of the symbiosis of Mijak woodcarving and so-called zographos painting of the 19th century. It has great importance for Serbian national history, the research of modern-age art in the Balkans and the phenomenology of visual culture and cults. Its study opens various questions concerning ktetorship, authorship, models, etc. Out of plethora of questions, this text focuses on the iconography of the painted medallions and its models. The coffin-reliquary of the holy king represents a rounded work of art decorated with images of holy Serbian rulers and church dignitaries, representing the most extensive gallery of this kind in 19th-century Serbian art.